Safe zone for lateral pin placement for external fixation of the distal humerus. Issue 5 (14th October 2019) - Tang, Lan; Yishake, Mumingjiang; Ye, Chenyi; Hade, Haisaier; Li, Zhanchun; He, Rongxin
Abstract : External fixation is a common, efficient technique used for humeral shaft stabilization and elbow fractures. There are reports of radial nerve injuries associated with this procedure. In this study, we investigated the course and variability of the radial nerve along the lateral humerus in relation to the elbow joint to determine a relatively safe zone for lateral pin placement in external fixation. Twenty upper extremities from 10 cadavers were studied. The nerve branches and course of the radial nerve along the lateral humerus were carefully dissected. Straight lines ( a, b, and c ) were made connecting three landmarks (the acromion, coracoid process, and anterior wall of the axilla) in the proximal upper extremity to the lateral condyle (LC) of the humerus; their intersections with the radial nerve ( A, B, and C ) were marked. We analyzed whether the intersection positions were correlated with the connecting line lengths. The mean lengths of the connecting lines were ( a ) 27.24 ± 2.57, ( b ) 26.18 ± 2.79, and ( c ) 20.95 ± 1.44 cm; the distance between the intersection points and the LC of the humerus were ( Aa ) 7.56 ± 1.31, ( Bb ) 6.90 ± 2.27, and ( Cc ) 5.01 ± 0.83 cm; and the measured intersection points of the radial nerve in the lateral aspect of the humerus were ( A ) 18.48%–34.82%, ( B ) 13.48%–40.00%, and ( C ) 19.27%–28.05% of the lengths of lines a, b, and c, respectively. Our data provide a more reliable reference to predict the course of the radial nerve on the lateral humerus and define a safe zone for pin placement. Clin. Anat., 33:637–642, 2020. © 2019 Wiley Periodicals, Inc.